THE INFLUENCE OF DIGITAL MARKETING ON PURCHASING DECISIONS AND CUSTOMER SATISFACTION ON ONLINE TRAVEL AGENT SERVICES - Didit Iswahyuniarto; Nafiah Ariyani; Levyda Levyda (Jurnal Ekonomi, 2023)
Online Travel Agent (OTA) is a website that sells travel products and services through digital marketing to customers. These OTA products include hotels, flights, travel packages, and car rentals. OTAs here are third parties that resell services on behalf of other businesses, including in the hospitality industry. The AISAS (Attention, Interest, Search, Action and Share) method is one of the methods or models designed to approach the target audience effectively by looking at behavioral changes that occur especially related to the background of advances in internet technology. This study used a descriptive statistical data analysis method. The presentation of descriptive statistical data is usually carried out in the form of graphs or tables. Descriptive statistics include average, maximum, minimum, and standard deviation. Digital Marketing OTAs expressed in (X) have a strong correlation to the dependent variable: Purchasing Decisions expressed in (Y1) which has an index correlation of 0.663 or 66.3%. The correlation of the influence of the Purchasing Decision variable (Y1) on the Customer Satisfaction variable (Y2) is significant because it has an index correlation of 0.633 or 63.3%, so it is stated that the correlation of the Y1 variable to the Y2 variable is strong. The customer decides to purchase OTA products after verifying certainty about the advantages in transactions such as prices, promotions and reservation fees are in line with expectations. The certainty of benefits and convenience when transacting based on information that is successfully tracked on the OTA website is the reason customers make purchase decisions. Product purchase transactions at selected Online Travel Agents (OTA) in terms of price, promotions and facilities are very profitable and customers are satisfied because their expectations have been met. The ease of accessing information about the benefits, benefits and transaction prices facilitated by the OTA digital marketing service of the customer's choice has met its expectations.